Tuberous sclerosis complex and diffuse lipomatosis: Case report of a rare association - Ankit Mittal; Keshavamurthy Vinay; Dipankar De; Sanjeev Handa; Anindita Sinha (Wolters Kluwer Medknow Publications, 2018)
Lipomatosis is characterized by diffuse infiltration of adipocytes in a tissue. A young male patient presented for evaluation of unilateral limb swelling. On evaluation, he was found to have tuberous sclerosis complex with diffuse lipomatosis of the right leg. To the best of the authors' literature search, only two previous reports of association of tuberous sclerosis complex with diffuse lipomatosis were found. The molecular mechanisms behind the co-occurrence of these two entities have not been studied in detail. Abnormalities in lipolysis and lipogenesis pathway may underlie the co-occurrence of tuberous sclerosis complex and diffuse lipomatosis.